HOME REMEDIES AND TRADITIONAL EYE MEDICINES USED FOR THE TREATMENT OF COMMON EYE AILMENTS IN DISTRICT SWABI - Iqbal, Asif; Orakzai, Omer Khan; Ayaz, Maqsood (Journal of Postgraduate Medical Institute, 2012)
Objectives: To identify the different home remedies and traditional eye medicines used for the treatment of different common eye ailments in District Swabi. Methodology: This was Cross Sectional study of fifteen months duration, from February 2010 to May 2011 conducted in out-patient department of District Headquarter Hospital Swabi. Initially different eye ailments and their home remedies and traditional eye medicines were identified by interviewing of the hospital staff belonging to different villages of district Swabi. 1500 patients, aged 20 years and above and also those patients who could answer were included in the study. Results: The study comprised of 1500 patients belonging to different villages of district swabi. The mean age of patients was 42.33 years, ranging from 20 yrs to 80 yrs.818(54.5%) patients were male and 682(45.5) patients were female. The male to female ratio was 1.2: 1 .At least 7 common eye ailments and 11 home remedies or traditional eye medicines commonly used were recognized. The different home remedies and traditional eye medicines used in different eye ailments included surma (galena- lead sulfide) (39.24%), alum(6.70%), honey(14.30%), coldwater (5.69%), ice cube(0.93%), rose water(2.33%), black pepper(1.28%), turmeric paste(5.85%), hot fomentation(5.37%), olive oil(4.94%), goat milk(0.87%) and different combinations of these home remedies and traditional eye medicines(12.50%). Conclusion: There is evidence of use of Home Remedies and Traditional Eye Medicines in Pakistan especially in rural population. Chemical substances and plant products are used frequently as Home Remedies and Traditional Eye Medicines.